Assembling of Platinum Nanoparticles on the Surface of Glassy Carbon Electrode using Different Electrochemical Method and its Catalysis for Oxygen - Song, Y.Z.; Song, Weihao; Zhang, X.; Cao, W.; Zhou, L.; Qian, L.; Ge, A. (Asian Journal of Chemistry, 2015)
In this paper, the platinum nanoparticles on the surface of glassy carbon electrode were synthesized by linear sweep voltammetry, differential pulse voltammetry, cyclic voltammetry and amperometric response, respectively. Electrochemical behaviour of oxygen at platinum nanoparticle modified glassy carbon electrode was investigated. It was demonstrated that the modification of glassy carbon electrode with platinum nanoparticles prepared by linear sweep voltammetry is a simple and effective method for obtaining highly sensitive sensor for determination of oxygen.